Self-supporting positive electrode and preparation method and application thereof
Through electrospinning technology, carbon nanofibers and positive electrode nanoactive materials are connected to a 3D Internet network, and a support positive electrode is prepared, which solves the shortcomings of the positive electrodes of sodium ion batteries in terms of flexibility and high energy density, and achieves excellent charge and discharge specific capacity and Coulomb efficiency.
Patent Information
- Application Number
- CN202411823445.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
The existing sodium ion battery positive electrodes have shortcomings in terms of flexibility and high energy density, which are difficult to meet the needs of wearable devices in humans.
Electrospinning technology is used to connect carbon nanofibers with positive electrode nanoactive materials (such as composite nanoparticles of carbon and Na3V2 (PO4)3) into a 3D Internet network to prepare a support positive electrode.
The conductivity and electrochemical stability of the composite electrode are improved, excellent charge and discharge specific capacity and Coulomb efficiency are achieved, and the use of current collectors, conductive agents and binders in traditional electrode preparation is avoided.
Smart Images

Figure CN119650601A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a self-supporting positive electrode and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have the advantages of high energy density, high operating voltage and long service life, and have been widely used in fields such as mobile phones, computers, portable electronic devices and electric vehicles. However, limited resource reserves and high costs still restrict the development of lithium-ion secondary batteries. Sodium-ion batteries have been widely studied because of their similar electrochemical properties and abundant resources to lithium-ion batteries. In recent years, with the continuous development of flexible electronic devices such as roll-up displays, electronic skins and wearable sensors, higher requirements have been put forward for flexible rechargeable batteries. Flexible batteries that meet the needs of human wearable devices must not only have high flexibility, high energy density and long service life, but also have high safety and low cost to meet the needs of large-scale commercial applications. Electrospinning is a relatively simple and low-cost method for preparing nanofibers, which has been widely used in the synthesis of energy storage and sensing materials in recent years. In particular, electrospun materials can be directly designed into interwoven nanofiber films, which are the most promising candidates in flexible battery components. One-dimensional nanomaterials such as nanowires and nanofibers have the advantages of high ion diffusion efficiency and direct charge transport as electrode materials. In addition, the flexible carbon nanofiber mesh synthesized by electrospinning and carbonization can be directly used as the electrode of the secondary battery, which can avoid the use of conductive agents, binders and fluid collectors, and has great advantages in improving the overall energy density of the battery and reducing costs. Its good flexibility also makes it have great application prospects in flexible batteries. Many studies on the application of electrospinning technology are aimed at loading some electrochemically active metal particles on nanocarbon fibers to improve the performance of the electrode. The Internet composed of one-dimensional fibers improves the conductivity of the composite material, and the carbon fiber coating can also alleviate the volume expansion of the metal particles during the charging and discharging process. In addition to electrodes, electrospun fibers are also used in solid polymer electrolytes. However, there is a lack of research on carbon composite fibers prepared by electrospinning as the positive electrode of sodium ion batteries. Summary of the invention
[0003] The purpose of the present invention is to provide a self-supporting positive electrode and a preparation method and application thereof. The preparation method can embed all or part of the positive electrode nano-active material into the interior of carbon fibers and staggeredly form a supporting network. The prepared self-supporting positive electrode has excellent charge and discharge specific capacity, coulombic efficiency and cycle stability.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing a self-supporting positive electrode, comprising the following steps:
[0006] mixing the positive electrode nano-active material, the solvent and the thickener to obtain an electrospinning precursor dispersion;
[0007] Electrospinning the electrospinning precursor dispersion to obtain a polymer fiber film precursor;
[0008] calcining the polymer fiber film precursor to obtain the self-supporting positive electrode;
[0009] The positive electrode nano active material includes composite nano particles of carbon and Na3V2(PO4)3 or composite nano particles of carbon and Na4Fe3(PO4)2(P2O7).
[0010] Preferably, the method for preparing the positive electrode nano-active material comprises the following steps:
[0011] Mixing a raw material for preparing the positive electrode nano-active material, a carbon source and water to obtain a mixed solution;
[0012] spray drying the mixed solution to obtain a nanoparticle precursor;
[0013] The nanoparticle precursor is calcined to obtain the positive electrode nano active material.
[0014] Preferably, the spray drying temperature is 140-280° C., and the spray drying feed rate is 200-500 mL / h.
[0015] Preferably, the mixing comprises:
[0016] After first mixing the positive electrode nano-active material and the solvent, adding the thickener;
[0017] The first mixing includes stirring and ultrasound performed sequentially;
[0018] The stirring time is 1 to 2 hours; the ultrasonic power is 300W and the time is 1 hour.
[0019] Preferably, the thickener is added under stirring;
[0020] The stirring temperature is 60-80°C and the stirring time is 2-4h;
[0021] The thickener is one or more of PAN, PVP and PVA;
[0022] The mass ratio of the positive electrode nano active material to the thickener is 1:(0.5-4).
[0023] Preferably, the capacity of the syringe used for the electrospinning is 10 mL, and the needle specification is 1.2×38 mm;
[0024] The environmental humidity in the spinning machine used in the electrostatic spinning is 30%, the working voltage is 15-20 kV, and the propulsion speed of the syringe is 0.5-1 mL / h.
[0025] Preferably, the distance between the needle of the syringe used in the electrospinning and the roller receiver is 10 to 20 cm, and the surface of the roller receiver is coated with copper foil or aluminum foil; the rotation speed of the roller receiver is 400 to 1000 rpm.
[0026] Preferably, the calcination includes a first calcination and a second calcination performed sequentially;
[0027] The first calcination is carried out in an air atmosphere, the temperature of the first calcination is 250-270° C., the time is 2-4 hours, and the heating rate is 3-5° C. / min;
[0028] The second calcination is carried out in a protective atmosphere, the temperature of the second calcination is 500-800° C., the time is 2-4 hours, and the heating rate is 3-5° C. / min.
[0029] The present invention also provides a self-supporting positive electrode prepared by the preparation method described in the above technical solution.
[0030] The present invention also provides the use of the self-supporting positive electrode described in the above technical solution in a sodium ion battery.
[0031] The present invention provides a method for preparing a self-supporting positive electrode, comprising the following steps: mixing a positive electrode nano-active material, a solvent and a thickener to obtain an electrospinning precursor dispersion; electrospinning the electrospinning precursor dispersion to obtain a polymer fiber film precursor; calcining the polymer fiber film precursor to obtain the self-supporting positive electrode; the positive electrode nano-active material comprises composite nano-particles of carbon and Na3V2(PO4)3 or composite nano-particles of carbon and Na4Fe3(PO4)2(P2O7). The present invention uses carbon nanofibers prepared by electrospinning to connect with positive electrode nano-active materials to form a 3D interconnected network, providing a fast transfer channel for ions and electrons, improving the conductivity of the composite electrode, and the coating of carbon fibers can also improve the electrochemical stability of the positive electrode nano-active material, effectively improving the cycle stability of the electrode. Therefore, the self-supporting positive electrode for sodium ion battery positive electrode prepared by the preparation method provided by the present invention can avoid the use of current collectors, conductive agents and binders in traditional electrode preparation, and has excellent charge and discharge specific capacity and coulomb efficiency. The sodium ion full battery assembled with the self-supporting positive electrode for sodium ion positive electrode provided by the present invention has an initial reversible charge and discharge capacity of up to 98.6 mAh / g at a charge and discharge current density of 1C. After 100 charge and discharge cycles, the coulomb efficiency is always above 98%, and the charge and discharge specific capacity can still be maintained at about 98.8 mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the preparation process of the self-supporting positive electrode of the present invention;
[0033] Figure 2 Thermogravimetric diagram of the positive electrode active material prepared by spray drying in Examples 1, 2 and 3;
[0034] Figure 3 This is the XRD pattern of the self-supporting positive electrode described in Example 1;
[0035] Figure 4 This is a SEM image of the self-supporting positive electrode described in Example 1;
[0036] Figure 5 The charge and discharge cycle curve of the button-type sodium ion battery described in Test Example 1;
[0037] Figure 6 The charge and discharge cycle curve of the button-type sodium ion battery described in Test Example 2;
[0038] Figure 7 The charge and discharge cycle curve of the button-type sodium ion battery described in Test Example 3;
[0039] Figure 8 Thermogravimetric diagram of the positive electrode active material prepared by spray drying as described in Example 4;
[0040] Fig. 9 is the XRD pattern of the self-supporting electrode described in Example 4;
[0041] Fig.10 is a SEM image of the self-supporting electrode described in Example 4;
[0042] Fig.11 This is the charge and discharge cycle curve of the button-type sodium ion battery described in Test Example 4. DETAILED DESCRIPTION
[0043] The present invention provides a method for preparing a self-supporting positive electrode, comprising the following steps:
[0044] mixing the positive electrode nano-active material, the solvent and the thickener to obtain an electrospinning precursor dispersion;
[0045] Electrospinning the electrospinning precursor dispersion to obtain a polymer fiber film precursor;
[0046] calcining the polymer fiber film precursor to obtain the self-supporting positive electrode;
[0047] The positive electrode nano active material includes composite nano particles of carbon and Na3V2(PO4)3 or composite nano particles of carbon and Na4Fe3(PO4)2(P2O7).
[0048] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0049] The present invention mixes positive electrode nano-active materials, solvents and thickeners to obtain an electrostatic spinning precursor dispersion; the positive electrode nano-active materials include composite nano-particles of carbon and Na3V2(PO4)3 or composite nano-particles of carbon and Na4Fe3(PO4)2(P2O7).
[0050] In the present invention, the method for preparing the positive electrode nano-active material preferably comprises the following steps:
[0051] Mixing a raw material for preparing the positive electrode nano-active material, a carbon source and water to obtain a mixed solution;
[0052] spray drying the mixed solution to obtain a nanoparticle precursor;
[0053] The nanoparticle precursor is calcined to obtain the positive electrode nano active material.
[0054] The invention mixes the raw material for preparing the positive electrode nano active material, the carbon source and water to obtain a mixed solution.
[0055] In the present invention, when the positive electrode nano-active material is Na3V2(PO4)3 nanoparticles (NVP), the raw materials for preparing the positive electrode nano-active material preferably include a sodium source, a vanadium source, a phosphorus source and a carbon source; the sodium source preferably includes one or more of sodium carbonate, sodium hydroxide, sodium dihydrogen phosphate and disodium hydrogen phosphate. When the sodium source is two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances; the vanadium source preferably includes ammonium metavanadate and / or vanadium pentoxide. When the vanadium source is ammonium metavanadate and vanadium pentoxide, the present invention has no special restrictions on the ratio of the above-mentioned two substances; the phosphorus source preferably includes one or more of ammonium dihydrogen phosphate, sodium dihydrogen phosphate and disodium hydrogen phosphate. When the phosphorus source is two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances.
[0056] In the present invention, when the positive electrode nano-active material is Na4Fe3(PO4)2(P2O7) nanoparticles (NFPP), the raw materials for preparing the positive electrode nano-active material preferably include a sodium source, an iron source, a phosphorus source and a carbon source; the sodium source preferably includes one or more of sodium dihydrogen phosphate, sodium citrate and sodium carbonate. When the sodium source is two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances; the iron source preferably includes one or more of ferric nitrate, ferrous oxalate and ferrous sulfate. When the iron source is two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio; the phosphorus source preferably includes one or more of sodium dihydrogen phosphate, ammonium dihydrogen phosphate and disodium hydrogen phosphate. When the phosphorus source is two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.
[0057] In the present invention, the carbon source preferably includes citric acid and / or oxalic acid. When the carbon source is citric acid and oxalic acid, the present invention has no special limitation on the ratio of citric acid and oxalic acid.
[0058] In the present invention, the role of the carbon source is to reduce the high-valent vanadium source and iron source to a low-valent state when the raw materials are mixed, and to convert them into carbon after calcination to improve the conductivity of the active material.
[0059] In the present invention, the usage ratio of the sodium source, the carbon source and water is preferably 100-75 mmol:50 mmol:400 mL.
[0060] In the present invention, the mixing process is preferably carried out under stirring conditions, the stirring time is preferably 1 to 2 hours, and the stirring speed is preferably 300 to 500 rpm.
[0061] After obtaining the mixed solution, the present invention spray-dries the mixed solution to obtain a nanoparticle precursor.
[0062] In the present invention, the spray drying temperature is preferably 140 to 280° C., more preferably 150 to 270° C.; the feed rate of the spray drying is preferably 200 to 500 mL / h, more preferably 250 to 350 mL / h.
[0063] In the present invention, the spray drying is used to spray the liquid material into mist particles, so that the water is evaporated quickly in the hot air, thereby obtaining a dry nanoparticle precursor. The rapid drying process can ensure the uniform distribution of each component in the precursor.
[0064] After obtaining the nanoparticle precursor, the present invention calcines the nanoparticle precursor to obtain the positive electrode nano active material.
[0065] In the present invention, when the positive electrode nano-active material is NVP, the calcination preferably includes a first step calcination and a second step calcination; the first step calcination is preferably carried out in an air atmosphere; the temperature of the first step calcination is preferably 340-360°C, more preferably 350°C; the time is preferably 3.8-4.2h, more preferably 4h; the heating rate is preferably 2-4°C / min, more preferably 3°C / min; the second step calcination is preferably carried out in an argon atmosphere; the temperature of the second step calcination is preferably 700-800°C, more preferably 750°C; the time is preferably 6-10h, more preferably 8h, and the heating rate is preferably 2-4°C / min, more preferably 3°C / min.
[0066] In the present invention, when the positive electrode nano-active material is NFPP, the calcination is carried out in a protective atmosphere, and the protective atmosphere is preferably a mixture of argon and hydrogen with a volume ratio of 90:10; the calcination temperature is preferably 450-600°C, more preferably 500°C; the time is preferably 4-10h, more preferably 5h; the heating rate is preferably 2-4°C / min, more preferably 3°C / min. .
[0067] In the present invention, the solvent is preferably DMF and / or acetone. When the solvent is DMF and acetone, the present invention has no special limitation on the ratio of DMF and acetone, and they can be mixed in any ratio.
[0068] In the present invention, the thickener is preferably one or more of PAN, PVP and PVA. When the thickener is two or more of the above specific selections, the present invention has no special limitation on the ratio of the above specific substances, and they can be mixed in any ratio.
[0069] In the present invention, the mixing preferably includes: first mixing the positive electrode nano-active material and the solvent, and then adding the thickener.
[0070] In the present invention, the first mixing preferably includes stirring and ultrasound performed in sequence; the stirring speed is preferably 300-500 rpm, more preferably 350-450 rpm, and most preferably 380-420 rpm; the stirring time is preferably 1-2 h, more preferably 1.2-1.8 h, and most preferably 1.4-1.6 h; the power of the ultrasound is preferably 300 W, and the time is preferably 1 h. In the present invention, the ultrasound is preferably performed in a cell crusher.
[0071] In the present invention, the thickener is preferably added under stirring; the stirring temperature is preferably 60-80°C, more preferably 65-75°C, most preferably 68-72°C; the time is preferably 2-4h, more preferably 2.5-3.5h, most preferably 2.8-3.2h.
[0072] In the present invention, the mass ratio of the positive electrode nano-active material to the thickener is preferably 1:(0.5-4). When the positive electrode nano-active material is NFPP, the mass ratio of the positive electrode nano-active material to the thickener is preferably 1:(0.5-2), and more preferably 1:0.5; when the positive electrode nano-active material is NVP, the mass ratio of the positive electrode nano-active material to the thickener is preferably 1:(1-4), more preferably 1:(1-3), and most preferably 1:1. In the present invention, the amount ratio of the thickener to the solvent is preferably 1:(8-9), more preferably 1:(8.2-8.8), and most preferably 1:(8.4-8.6).
[0073] After adding the thickener, the present invention also preferably includes natural cooling.
[0074] In the present invention, the thickener has the following functions: 1) as a skeleton material to provide mechanical strength for the electrode to achieve the purpose of self-support; 2) as a carbon source to form a conductive carbon network during the calcination process to replace the current collector.
[0075] After obtaining the electrospinning precursor dispersion, the present invention electrospins the electrospinning precursor dispersion to obtain a polymer fiber film precursor.
[0076] In the present invention, the capacity of the syringe used for electrospinning is preferably 10 mL, and the needle specification is preferably 1.2×38 mm. The syringe is preferably a medical syringe.
[0077] In the present invention, the ambient humidity in the spinning machine used for the electrospinning is preferably 30%, the working voltage is preferably 15-20 kV, more preferably 16-19 kV, and most preferably 17-18 kV; the propulsion speed of the syringe is preferably 0.5-1 mL / h, more preferably 0.6-0.9 mL / h, and most preferably 0.7-0.8 mL / h; the distance between the needle of the syringe used for the electrospinning and the roller receiver is preferably 10-20 cm, more preferably 12-18 cm, and most preferably 14-16 cm; the surface of the roller receiver is preferably coated with copper foil or aluminum foil; the rotation speed of the roller receiver is preferably 400-1000 rpm, more preferably 500-900 rpm, and most preferably 700-800 rpm.
[0078] After the electrospinning, the present invention also preferably includes drying; the drying temperature is preferably 60-80°C, more preferably 65-75°C, most preferably 68-72°C; the time is preferably 8-12h, more preferably 9-11h, most preferably 10h. In the present invention, the drying is preferably carried out in a blast drying oven.
[0079] In the present invention, the purpose of controlling the above-mentioned electrospinning conditions within the above-mentioned range is to control the spinning precursor solution to reach a suitable viscosity and conductivity, so that the solution can form a stable Taylor cone at the needle tip in the electrostatic field, form a jet under the action of the electric field force and surface tension, and quickly evaporate and dry in the air to form uniform nanofibers.
[0080] After obtaining the polymer fiber film precursor, the present invention calcines the polymer fiber film precursor to obtain the self-supporting positive electrode.
[0081] In the present invention, the calcination preferably includes a first calcination and a second calcination carried out sequentially; the first calcination is preferably carried out in an air atmosphere, the temperature of the first calcination is preferably 250-270°C, more preferably 255-265°C, and most preferably 258-262°C; the time is preferably 2-4h, more preferably 2.5-3.5h, and most preferably 2.8-3.2h; the heating rate is preferably 3-5°C / min, more preferably 3°C / min. In the present invention, the first calcination is preferably carried out in a muffle furnace. After the first calcination is completed, the present invention also preferably includes cooling. The present invention does not have any special limitation on the cooling process, and the process well known to those skilled in the art can be used. In the present invention, the second calcination is preferably carried out in a protective atmosphere, and the protective atmosphere is preferably argon or nitrogen; the temperature of the second calcination is preferably 600-800°C, more preferably 650-750°C, and most preferably 680-720°C; the time is preferably 2-4h, more preferably 2.5-3.5h, and most preferably 2.8-3.2h; the heating rate is preferably 3-5°C / min, more preferably 3.5-4.5°C / min, and most preferably 3.8-4.2°C / min. In the present invention, the second calcination is preferably carried out in a tubular furnace.
[0082] In the present invention, preferably no grinding is performed during the calcination process.
[0083] In the present invention, the first calcination is used to maintain the structural stability of the polymer precursor prepared by electrospinning through a pre-oxidation process in an air atmosphere, and the second calcination is used to carbonize the precursor fiber at a high temperature under oxygen-free conditions to form a conductive carbon network.
[0084] The present invention also provides a self-supporting positive electrode prepared by the preparation method described in the above technical solution.
[0085] The present invention also provides the use of the self-supporting positive electrode described in the above technical solution in a sodium ion battery. The present invention does not have any special limitation on the method of the application, and the method well known to those skilled in the art can be used.
[0086] The self-supporting positive electrode and its preparation method and application provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0087] Example 1
[0088] Preparation process Figure 1As shown, 50mmol NH4VO3 and 50mmol anhydrous citric acid are dissolved in 400mL water and heated and stirred at 80℃ for 1h until the solution turns dark blue, then 75mmol NH4H2PO4 and 37.5mmol Na2CO3 are added, stirred on a stirring table for 1h to mix evenly, and then the mixed solution is dried into a nanoparticle precursor at a drying temperature of 150℃ and a feed rate of 300mL / h using a spray dryer. The dried nanoparticle precursor is calcined in two steps (the first step of calcination is carried out in a muffle furnace, the calcination temperature is 350℃, the time is 4h, and the heating rate is 3℃ / min, and the second step of calcination is carried out in a tubular furnace, the protective atmosphere is argon, the calcination temperature is 750℃, the time is 8h, and the heating rate is 3℃ / min) to obtain the positive electrode nano-active material (including carbon and Na3V2(PO4)3(NVP) with a mass ratio of 9:89.3), by Figure 2 It can be seen that the mass reduction before 300 degrees Celsius is the water content of 1.7%, and the mass reduction before 350-600 degrees Celsius is the mass reduced by carbon combustion, that is, the carbon content is 9%; therefore, the mass ratio of carbon to NVP can be calculated to be 9:89.3);
[0089] 0.6 g of the positive electrode nanoactive material was dispersed in 5 mL of DMF and stirred on a stirring table for 1 h. The obtained positive electrode nanoactive material dispersion was then transferred to a cell crusher and ultrasonically dispersed at a power of 300 W for 1 h. 0.6 g of PAN was added and stirred on a heated stirring table (temperature of 70° C. for 1 h). The mixture was allowed to stand at room temperature until naturally cooled to obtain an electrospinning precursor dispersion.
[0090] The electrospinning precursor dispersion is transferred into an electrospinning syringe pump (the syringe pump is a medical syringe with a volume of 10 mL, and the syringe needle has a specification of 1.2 mm×38 mm), the syringe pump is installed on the electrospinning machine, and the syringe pump is pushed at a speed of 0.8 mL / h; after electrospinning (the ambient humidity of the electrospinning machine is 30%, the working voltage is 18 kV, a drum receiver is used, the receiver is wrapped with aluminum foil, and rotates at a speed of 400 rpm, and the distance between the drum receiver and the syringe pump needle is 15 cm), the polymer fiber film precursor is collected from the aluminum foil outside the drum receiver;
[0091] The polymer fiber film precursor is placed in an electric hot air drying oven for drying (60°C, 8h) to remove the organic solvent remaining in the precursor. After drying, the precursor is placed in a corundum ark and calcined for the first time in a muffle furnace (air atmosphere). The temperature of the first calcination is 250°C, the time is 2h, and the heating rate is 5°C / min. The precursor after the first calcination is collected and placed in a tube furnace for the second calcination (argon atmosphere). The temperature of the second calcination is 700°C, the time is 2h, and the heating rate is 5°C / min. After the calcination is completed, it is cut according to the needs to obtain a self-supporting positive electrode;
[0092] The self-supporting positive electrode was subjected to an X-ray diffraction test, and the test results were as follows: Figure 3 As shown by Figure 3 It can be seen that the peaks in the XRD pattern match the typical NVP peaks, and there is a bulge between 20° and 30°, which comes from the carbon nanofibers that serve as the main self-supporting structure during the electrospinning process;
[0093] The self-supporting positive electrode was tested by scanning electron microscope. The test results are as follows Figure 4 As shown by Figure 4 It can be seen that a large number of carbon nanofibers with a diameter of about 1 μm are loaded with NVP particles. The carbon nanofibers are interconnected to form a carbon nanofiber network, which becomes the skeleton of the self-supporting structure of the material and plays the function of a current collector.
[0094] Test Example 1
[0095] The self-supporting positive electrode, negative electrode (the type of negative electrode is a metal sodium sheet), electrolyte (the electrolyte is 1M NaClO4 dissolved in a mixed solution of ethylene carbonate / diethyl carbonate (EC / DEC) with a volume ratio of 1:1, and the mixed solution of ethylene carbonate / diethyl carbonate (EC / DEC) contains 5wt% of fluoroethylene carbonate), separator (the type of separator is glass fiber Whatman GF / D) and accessories (the accessories are CR2032 battery shell kit) described in Example 1 are assembled into a button-type sodium ion battery;
[0096] The button-type sodium ion battery was tested under the conditions of room temperature and constant temperature, with a voltage range of 2.5 to 3.8 V and a test current density of 1 C. The test results are as follows: Figure 5 As shown by Figure 5 It can be seen that the sodium ion full battery has an initial reversible specific capacity of 98.5 mAh / g and a coulombic efficiency of 97.9% at a charge and discharge current density of 1C; with the increase in the number of charge and discharge cycles, after 100 charge and discharge cycles, the reversible specific capacity still remains at around 98.8 mAh / g.
[0097] Example 2
[0098] Preparation process Figure 1 As shown, 50mmol NH4VO3 and 50mmol anhydrous citric acid are dissolved in 400mL water and heated and stirred at 80℃ for 1h until the solution turns dark blue, then 75mmol NH4H2PO4 and 37.5mmol Na2CO3 are added, stirred on a stirring table for 1h to mix evenly, and then the mixed solution is dried into a nanoparticle precursor at a feed rate of 300mL / h at a drying temperature of 150℃ using a spray dryer. The dried nanoparticle precursor is calcined in two steps (the first step of calcination is carried out in a muffle furnace, the calcination temperature is 350℃, the time is 4h, and the heating rate is 3℃ / min, and the second step of calcination is carried out in a tubular furnace, the protective atmosphere is argon, the calcination temperature is 750℃, the time is 8h, and the heating rate is 3℃ / min), and the positive electrode nano active material (including carbon and Na3V2(PO4)3(NVP) with a mass ratio of 9:89.3) is obtained;
[0099] 0.3 g of the positive electrode nanoactive material was dispersed in 5 mL of DMF and stirred on a stirring table for 1 h. The obtained positive electrode nanoactive material dispersion was then transferred to a cell crusher and ultrasonically dispersed at a power of 300 W for 1 h. 0.6 g of PAN was added and stirred on a heated stirring table (temperature of 70° C. for 1 h). The mixture was allowed to stand at room temperature until naturally cooled to obtain an electrospinning precursor dispersion.
[0100] The electrospinning precursor dispersion is transferred into an electrospinning syringe pump (the syringe pump is a medical syringe with a volume of 10 mL, and the syringe needle has a specification of 1.2 mm×38 mm), the syringe pump is installed on the electrospinning machine, and the syringe pump is pushed at a speed of 0.8 mL / h; after electrospinning (the ambient humidity of the electrospinning machine is 30%, the working voltage is 18 kV, a drum receiver is used, the receiver is wrapped with aluminum foil, and rotates at a speed of 400 rpm, and the distance between the drum receiver and the syringe pump needle is 15 cm), the polymer fiber film precursor is collected from the aluminum foil outside the drum receiver;
[0101] The polymer fiber film precursor is placed in an electric heated forced air drying oven for drying (60°C, 8h) to remove the organic solvent remaining in the precursor. After drying, the precursor is placed in a corundum ark and subjected to the first calcination in a muffle furnace (air atmosphere). The temperature of the first calcination is 250°C, the time is 2h, and the heating rate is 5°C / min. The precursor after the first calcination is collected and placed in a tubular furnace for the second calcination (argon atmosphere). The temperature of the second calcination is 700°C, the time is 2h, and the heating rate is 5°C / min. After calcination, it is cut as required to obtain a self-supporting positive electrode.
[0102] Test Example 2
[0103] Referring to the process of Test Example 1, the self-supporting positive electrode described in Example 2 was assembled into a button-type sodium ion battery and tested. The test conditions were also referred to Test Example 1. The test results are as follows: Figure 6 As shown by Figure 6 It can be seen that the sodium ion battery has an initial reversible specific capacity of 98.6 mAh / g and a coulombic efficiency of 98.7% at a charge and discharge current density of 1C; as the number of charge and discharge times increases, after 100 charge and discharge cycles, the reversible specific capacity still remains at around 99.2 mAh / g.
[0104] Example 3
[0105] Preparation process Figure 1 As shown, 50mmol NH4VO3 and 50mmol anhydrous citric acid are dissolved in 400mL water and heated and stirred at 80℃ for 1h until the solution turns dark blue, then 75mmol g NH4H2PO4 and 37.5mmol Na2CO3 are added, stirred on a stirring table for 1h to mix evenly, and then the mixed solution is dried into a nanoparticle precursor at a feed rate of 300mL / h at a drying temperature of 150℃ using a spray dryer. The dried nanoparticle precursor is calcined in two steps (the first step of calcination is carried out in a muffle furnace, the calcination temperature is 350℃, the time is 4h, and the heating rate is 3℃ / min, and the second step of calcination is carried out in a tubular furnace, the protective atmosphere is argon, the calcination temperature is 750℃, the time is 8h, and the heating rate is 3℃ / min), and the positive electrode nano active material (including carbon and Na3V2(PO4)3(NVP) with a mass ratio of 9:89.3) is obtained;
[0106] 0.2 g of the positive electrode nanoactive material was dispersed in 5 mL of DMF and stirred on a stirring table for 1 h. The obtained positive electrode nanoactive material dispersion was then transferred to a cell crusher and ultrasonically dispersed at a power of 300 W for 1 h. 0.6 g of PAN was added and stirred on a heated stirring table (temperature of 70° C. for 1 h). The mixture was allowed to stand at room temperature until naturally cooled to obtain an electrospinning precursor dispersion.
[0107] The electrospinning precursor dispersion is transferred into an electrospinning syringe pump (the syringe pump is a medical syringe with a volume of 10 mL, and the syringe needle has a specification of 1.2 mm×38 mm), the syringe pump is installed on the electrospinning machine, and the syringe pump is pushed at a speed of 0.8 mL / h; after electrospinning (the ambient humidity of the electrospinning machine is 30%, the working voltage is 18 kV, a drum receiver is used, the receiver is wrapped with aluminum foil, and rotates at a speed of 400 rpm, and the distance between the drum receiver and the syringe pump needle is 15 cm), the polymer fiber film precursor is collected from the aluminum foil outside the drum receiver;
[0108] The polymer fiber film precursor is placed in an electric heated forced air drying oven for drying (60°C, 8h) to remove the organic solvent remaining in the precursor. After drying, the precursor is placed in a corundum ark and subjected to the first calcination in a muffle furnace (air atmosphere). The temperature of the first calcination is 250°C, the time is 2h, and the heating rate is 5°C / min. The precursor after the first calcination is collected and placed in a tubular furnace for the second calcination (argon atmosphere). The temperature of the second calcination is 700°C, the time is 2h, and the heating rate is 5°C / min. After calcination, it is cut as required to obtain a self-supporting positive electrode.
[0109] Test Example 3
[0110] Referring to the process of Test Example 1, the self-supporting positive electrode described in Example 3 was assembled into a button-type sodium ion battery and tested. The test conditions were also referred to Test Example 1. The test results are as follows: Figure 7 As shown by Figure 7 It can be seen that the sodium ion battery has an initial reversible specific capacity of 80.9 mAh / g and a coulombic efficiency of 70.64% at a charge and discharge current density of 1C; with the increase in the number of charge and discharge cycles, after 100 charge and discharge cycles, the reversible specific capacity still remains at around 88.9 mAh / g.
[0111] Example 4
[0112] Preparation process Figure 1 As shown, 75mmol Fe(NO3)3·9H2O, 100mmol NaH2PO4·2H2O and 50mmol anhydrous citric acid were dissolved in 400mL water, stirred on a stirring table for 1h to mix evenly, and then the mixed solution was dried into a nanoparticle precursor at a drying temperature of 270°C and a feed rate of 300ml / h using a spray dryer. The dried nanoparticle precursor was calcined (in a tubular furnace, the protective atmosphere was an argon-hydrogen mixture (90:10), the calcination temperature was 500°C, the time was 5h, and the heating rate was 3°C / min) to obtain a positive electrode nanoactive material (according to Figure 7The thermogravimetric diagram shows that the weight loss before 150 degrees Celsius is 5.6% of water evaporation, 150-350 degrees Celsius is the decomposition of NFPP, and 350-500 degrees Celsius is the combustion loss of carbon 6.1%. The positive electrode nano-active material includes carbon and Na4Fe3(PO4)2(P2O7)(NFPP) in a mass ratio of 6.1:88.3;
[0113] Subsequently, 1.2 g of the positive electrode nanoactive material was dispersed in 5 mL of DMF and stirred on a stirring table for 1 h. The obtained positive electrode nanoactive material dispersion was then transferred to a cell crusher and ultrasonically dispersed at a power of 300 W for 1 h. 0.6 g of PAN was added and stirred on a heated stirring table (temperature of 70° C. for 1 h), and allowed to stand at room temperature until naturally cooled to obtain an electrospinning precursor dispersion.
[0114] The electrospinning precursor dispersion is transferred into an electrospinning syringe pump (the syringe pump is a medical syringe with a volume of 10 mL, and the syringe needle has a specification of 1.2 mm×38 mm), the syringe pump is installed on the electrospinning machine, and the syringe pump is pushed at a speed of 0.8 mL / h; after electrospinning (the ambient humidity of the electrospinning machine is 30%, the working voltage is 18 kV, a drum receiver is used, the receiver is wrapped with aluminum foil, and rotates at a speed of 400 rpm, and the distance between the drum receiver and the syringe pump needle is 15 cm), the polymer fiber film precursor is collected from the aluminum foil outside the drum receiver;
[0115] The polymer fiber film precursor is placed in an electric hot air drying oven for drying (60°C, 8h) to remove the organic solvent remaining in the precursor. After drying, considering the oxidizing property of the active substance, some adjustments are made to the calcination process, which is mainly reflected in the first stage of calcination being carried out in a tubular furnace (argon atmosphere), the first calcination temperature is 250°C, the time is 2h, and the heating rate is 3°C / min; the second calcination continues to be carried out in a tubular furnace (argon atmosphere), the second calcination temperature is 600°C, the time is 2h, and the heating rate is 3°C / min. After calcination, it is cut according to demand to obtain a self-supporting electrode.
[0116] The self-supporting electrode was subjected to an X-ray diffraction test, and the test results were as follows: Fig. 9 As shown by Fig. 9 It can be seen that the peaks in the XRD pattern match the typical NFPP peaks, and there is a bulge between 20° and 30°, which comes from the carbon nanofibers that serve as the main self-supporting structure during the electrospinning process;
[0117] The self-supporting electrode was subjected to a scanning electron microscope test. The test results are as follows Fig.10 As shown by Fig.10It can be seen that NFPP particles are carried on carbon nanofibers with a diameter of more than 0.5 μm, and the carbon nanofibers are interconnected to form a carbon nanofiber network, which becomes the skeleton of the self-supporting structure of the material and also plays the function of a current collector.
[0118] Test Example 4
[0119] The self-supporting electrode described in Example 4, the negative electrode (the type of the negative electrode is a metal sodium sheet), the electrolyte (the electrolyte is 1M NaClO4 dissolved in a mixed solution of ethylene carbonate / diethyl carbonate (EC / DEC) with a volume ratio of 1:1, and the mixed solution of ethylene carbonate / diethyl carbonate (EC / DEC) contains 5wt% of fluoroethylene carbonate), the separator (the type of the separator is glass fiber Whatman GF / D) and the accessories (the accessories are CR2032 battery shell kit) are assembled into a button-type sodium ion battery;
[0120] The button-type sodium ion battery was tested under the conditions of room temperature and constant temperature, with a voltage range of 1.5 to 3.5 V and a test current density of 1C. The test results are as follows: Fig.11 As shown by Fig.11 It can be seen that the sodium ion full battery has an initial reversible specific capacity of 99.0 mAh / g and a coulombic efficiency of 88.55% at a charge and discharge current density of 1C; with the increase in the number of charge and discharge cycles, after 100 charge and discharge cycles, the reversible specific capacity still remains at around 97.7 mAh / g.
[0121] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a self-supporting positive electrode, characterized in that: The following steps are involved: mixing the positive electrode nano-active material, the solvent and the thickener to obtain an electrospinning precursor dispersion; Electrospinning the electrospinning precursor dispersion to obtain a polymer fiber film precursor; calcining the polymer fiber film precursor to obtain the self-supporting positive electrode; The positive electrode nano active material includes composite nano particles of carbon and Na3V2(PO4)3 or composite nano particles of carbon and Na4Fe3(PO4)2(P2O7).
2. The preparation method according to claim 1, characterized in that The method for preparing the positive electrode nano active material comprises the following steps: Mixing a raw material for preparing the positive electrode nano-active material, a carbon source and water to obtain a mixed solution; spray drying the mixed solution to obtain a nanoparticle precursor; The nanoparticle precursor is calcined to obtain the positive electrode nano active material.
3. The preparation method according to claim 2, characterized in that: The temperature of the spray drying is 140-280° C., and the feed rate of the spray drying is 200-500 mL / h.
4. The preparation method according to claim 1, characterized in that: The mixing includes: After first mixing the positive electrode nano-active material and the solvent, adding the thickener; The first mixing includes stirring and ultrasound performed sequentially; The stirring time is 1 to 2 hours; the ultrasonic power is 300W and the time is 1 hour.
5. The preparation method according to claim 4, characterized in that: Adding the thickener is carried out under stirring; The stirring temperature is 60-80°C and the stirring time is 2-4h; The thickener is one or more of PAN, PVP and PVA; The mass ratio of the positive electrode nano active material to the thickener is 1:(0.5-4).
6. The preparation method according to any one of claims 1 to 5, characterized in that: The capacity of the syringe used in the electrospinning is 10 mL, and the needle specification is 1.2×38 mm; The environmental humidity in the spinning machine used in the electrostatic spinning is 30%, the working voltage is 15-20 kV, and the propulsion speed of the syringe is 0.5-1 mL / h.
7. The preparation method according to claim 6, characterized in that: The distance between the needle of the syringe used in the electrospinning and the roller receiver is 10-20 cm, and the surface of the roller receiver is coated with copper foil or aluminum foil; the rotation speed of the roller receiver is 400-1000 rpm.
8. The preparation method according to claim 1, characterized in that: The calcination includes a first calcination and a second calcination performed sequentially; The first calcination is carried out in an air atmosphere, the temperature of the first calcination is 250-270° C., the time is 2-4 hours, and the heating rate is 3-5° C. / min; The second calcination is carried out in a protective atmosphere, the temperature of the second calcination is 500-800° C., the time is 2-4 hours, and the heating rate is 3-5° C. / min.
9. A self-supporting positive electrode prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the self-supporting positive electrode according to claim 9 in a sodium ion battery.